A Closer Look of How Individual Investor Make Investment Decision: Systematic Review - Rosyidah Rahmah; Nugraha; Disman; Imas Purnamasari (Atestasi : Jurnal Ilmiah Akuntansi, 2023)
The aim of this study is to examine the existing literature on the factors that influence the investment decisions made by individual investors. The employed methodology is a systematic literature review conducted using the PRISMA approach. The choice of Scopus as the information source was based on its status as the largest and well reputable scientific database. We obtained data from internet databases that contain extensive collections of scholarly studies, journal articles, and conference papers. These resources are written in English and are readily available to the authors. Using a predetermined string, 275 articles were extracted from Scopus. Ultimately, 137 papers were found to fit the criteria for analysis in discussing the factors that determine investing decisions for individual investors. The result show that there are five main determinant of investment decision for individual investor: Financial literacy, emotional biases, gender, generation y and long-term orientation. The implications of this study will be discussed later.